GENDER – BASED VIOLENCE IN CHIMAMANDA NGOZI ADICHIE’S PURPLE HIBISCUS - Osée, MUKASEREKA KHIKENZA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Among the plagues surrounding the world today, the most crucial is Gender – based violence. Women and girls are subject of many atrocities, physically, morally and psychologically. Women’s body has become a weapon in battlefield. Women are wildly violated by all kinds of categories of men in society: soldiers, Statesmen, businessmen, etc… Teenagers are savagely violated and sometimes bear undesirable pregnancies which lead either to fistula or death during the birthday. Chimamanda Ngozi Adichie, the author of “Purple Hibiscus” is against the so – called fathers or chiefs of families who still practice domestic violence in maltreating their children and partners (wives).